Concepts Related to Childhood and Demeanors of The Bodhisattva in Mahanipata Jataka Attakatha - Srion, Suddhinan (Journal of Graduate MCU KhonKaen Campus, 2019)
The purpose of this article is to study the concepts related to the childhood and demeanors of the Bodhisattva in the Mahanipata Jataka Attakathain the scope of 10 stories. Selected incarnations of the Bodhisattva for the study are; Phratemiya, PhraSuwansam and PraMahosod. The investigation has revealed the intellectual qualities displayed in childhood of the Bodhisattva incarnatesand that intelligent children are not inferior to adults and thus deserve to be respected. The childhood of the bodhisattva incarnatesillustrates the space made available for children in Buddhist literature – their existence and their abilities. The stories have pointed out conflicts between children and adults and by giving children a chance to express themselves and explain, adults could find their ideas and demeanors agreeable. The ancient literature of the Bodisattva recognizes the role of children and listens to their voices. Through the characters which are in their childhood, yet intelligent and virtuous, the Mahanipata Jataka Attakatha subtly gives a message that adults should allow children to show their potentials and extend the admiration they deserve.